Overlooking The Fantasy Genre In Soul Movie (2020) - Bimantara, Wismoyo; Fithratullah, Muhammad (Berumpun: International Journal of Social, Politics, and Humanities, 2024)
This study explores the relationship between fantasy genres in Disney Pixar's 2020 film Soul Movie, utilizing John G. Cawelti's genre theory as a central framework. Using Cawelti's theory as a guide, the research looks at how Soul movie genres present an imaginary world like the Great Beyond and Great Before to demonstrate fantasy features. This analysis expands the concept of genre in movies by examining important sequences, dialogue, and common representations. It also shows how the film mirrors established genre traditions. Additionally, the study examines the body of literature on sorting formulas, adding to the larger discussion on the role of genre in creating contemporary social narratives. The data reveals that whereas the strong settings are dominated by fantastical elements, promoting an open seeing encounter that requests over age group